Pengaruh Faktor Eksposi Terhadap Respon Detektor Isian Gas Pada Surveymeter Berbasis IoT - Chandra Kusuma; Diah Rahayu Ningtias (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
A surveymeter is a measuring instrument that functions to detect radiation exposure doses, which uses a Geiger Muller gas filled detector with the initial unit of sievert converted to microsievert (μSv/hour). In this research, we fabricated an IoT-based surveymeter and tested the response of the gas fill detector used to changes in exposure factors. Before collecting data, it is mandatory to set parameters on the control panel to determine the radiation exposure dose to be measured. Measurements are carried out on a mobile X-Ray with parameter settings including tube voltage (kV), tube current (mA), and exposure time (s). From the results of research that the Geiger Muller gas filled detector responds to the radiation exposure dose that has been determined on the control panel and fired by mobile X-Ray, the results detected by the detector will be displayed in the application in the form of Counts Per Minute (CPM), µSv/h, + /- and data can be stored in the database. The higher the tube current value given, the smaller the radiation dose value obtained. In other words, the gas fill detector responds with a dose value that is directly proportional to the X-ray tube voltage value and inversely proportional to the X-ray tube current value.